Study on the asynchronous performance of changing‐poles BDFM with the field‐circuit coupled based on the time‐stepping finite element analysis. Issue 9 (2nd July 2019) - Kan, Chaohao; Chu, Chenglong; Hu, Yang; Zhao, Wei
Abstract: The changing‐poles brushless doubly fed motor (the changing‐poles motor) has a special stator and rotor structure and two different operating states, so the finite element model of a conventional alternating current motor is not suitable. To establish a suitable model, this article first analyzes the coupling circuit, T‐shape equivalent circuit, and the phase diagram of the motor in the starting state, and the basic equivalent circuit of the motor in the running state is analyzed as well. Then, the design example of the prototype is introduced and the principle of the composite coil is explained by using the rotor‐winding extension diagram. Based on the above analyses, a two‐dimensional finite element model of field circuit coupling for the changing‐poles motor is established. In the calculation process of the direct presence of the model, the core saturation problem is considered and the coupling and constraint equations are adopted to deal with the rotor rotation problem, without the need to replan the placement of the rotor. Therefore, the calculation results are more accurate. Finally, by comparing the simulation results of a conventional finite element model, the simulation results of the time‐stepping finite element model, and the prototype test results, it is found that the time‐stepping finite element model is accurate and the simulation results fit well with the experimental results. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.